Efficiency of the enterprise resources usage: practical aspect - Abernikhina, Iryna; Sokyrykska, Iryna (Herald of Economics, 2020)
Introduction. Under the crisis circumstances in the economy an important task for enterprises is to consolidate and sometimes expand their position in the market. In this context, it is important to analyze the indicators of resource use, that allow to assess their use level and identify areas to help improve their efficiency.Methods. The theoretical basis of the study is the scientific publications of domestic and foreign scholars to assess the effectiveness of the enterprise resources usage. The results are obtained through the methods: analysis – in the study of basic theoretical, methodological approaches to assessing the efficiency of resource use; abstraction –   to determine the essential characteristics of the key indicators of resource efficiency; generalization – to systematize indicators for the efficiency assessment of enterprise resources use. The purpose is to search the directions to increase the efficiency of resources use in the conditions of an enterprise economic activity on the basis of the recent methodical achievements.Results. A thorough analysis of indicators for assessing the enterprise resources effectiveness on the basis of domestic and foreign scientists study is realized. It is proposed to systematize the most common indicators in order to assess the enterprise resources efficiency in quantitative terms into three groups: relative indicators of business activity (turnover ratios), indicators of resource management efficiency (turnover duration) and indicators of company assets efficiency for profit generation (profitability). An improved system of indicators has been applied to assess the resource use efficiency in the conditions of a real enterprise. Perspectives. Prospects for further research are to establish the degree of efficiency influence of enterprise resources use on the profit level with the mathematical models.